Price Trend and Price Spread Analysis of Cotton in Virudhunagar District, Tamil Nadu - Banumathy, S. (Indian Journal of Marketing, 2005)
Agriculture today occupies a very important and unique place in the economy of India. Now-a-days, it is considered as an industry supplying food materials to the millions and basic raw materials such as cotton, jute, sugarcane etc., for industrial development. It promotes rural employment, increases income and enhances the socio-economic status of the farmers. In short, agriculture in India, not only decides the economy of the country, but also determines its industrial development. Cotton is a commodity of global economic significance. It is an income and employment generating crop. Cotton and textiles, being the dominant sectors of Indian economy, they sustain directly or indirectly the livelihood of about seven million people. In India's annual report, nearly 335 was being contributed by cotton and textile products.